Is tRNA Binding or tRNA Mimicry Mandatory for Translation Factors? - Kristensen, O.; Laurberg, M.; Liljas, A.; Selmer, M. (Current Protein and Peptide Science, 2002)
tRNA is the adaptor in the translation process. The ribosome has three sites for tRNA, the A-, P-, and E-sites. The tRNAs bridge between the ribosomal subunits with the decoding site and the mRNA on the small or 30S subunit and the peptidyl transfer site on the large or 50S subunit. The possibility that translation release factors could mimic tRNA has been discussed for a long time, since their function is very similar to that of tRNA. They identify stop codons of the mRNA presented in the decoding site and hydrolyse the nascent peptide from the peptidyl tRNA in the peptidyl transfer site. The structures of eubacterial release factors are not yet known, and the first example of tRNA mimicry was discovered when elongation factor G (EF-G) was found to have a closely similar shape to a complex of elongation factor Tu (EF-Tu) with aminoacyl-tRNA. An even closer imitation of the tRNA shape is seen in ribosome recycling factor (RRF). The number of proteins mimicking tRNA is rapidly increasing. This primarily concerns translation factors. It is now evident that in some sense they are either tRNA mimics, GTPases or possibly both.
Keywords: tRNA Binding